(untitled) (Fiep Bulletin - online, 2017)
Acute transverse myelitis is a rare disease with few studies, characterized as a focal inflammatory demyelinatingdisorder of the spinal cord. While the studies and research, there are few theoretical allusive reference to clinical approaches,much less on the practices in the school environment. Thus, this study aims to seek in sport situations that encourage childrenengine development and adolescents with acute transverse myelitis, as well as forms of integration and respect for individuals.For this, we conducted a case study, where there were interventions. As a result, we observed improvements in self-esteem,enhanced muscle tone, decreased frames pain, preservation of balance, participation of sports games. Thus, we can concludethe importance of the role of schools, mainly in physical education classes to improve the quality of life of children andadolescents with acute transverse myelitis